Peaceful passages : a hospice nurse's stories of dying well - Wehr, Janet (Quest Books/Theosophical Publishing House, 2015)
"Joy is a word rarely associated with death. Yet joy is ultimately the effect in this collection of stories about Janet Wehr's experiences in witnessing the death of her patients during her fifteen years as a hospice nurse. Her first-hand account gives illuminating and comforting insight into the spiritual aspect of what occurs in the transition between life and death, highlighting the importance of the mind-body-spirit connection as it manifests in the dying process. It also gives a candid impression of hospices and hospice nurses and the services they can provide.All of Janet's forty-six personal stories are true, fascinating, heart-felt, and thought-provoking. Through her authentic examples, readers gain understanding, hope, and a sense of peace about what is, after all, an inevitable experience for us all. And with that sense of peace, comes joy.This book is endorsed by the President of Hospice of America and will be used as a training manual by that organization"--